2022
DOI: 10.5001/omj.2022.36
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Haplotype ATP-binding Cassette B1 and Glutathione S-transferase P1 A313G Genes with Hematological Toxicity in Indonesian Breast Cancer Patients Receiving Chemotherapy

Abstract: Objectives: Hematological toxicity induced by chemotherapy is known to be caused by multiple factors, including genetic factors, such as polymorphisms. The polymorphisms may occur in drug efflux transporter proteins and enzymes involved in drug metabolism. In our study, we investigate the incidence of hematological toxicities and its relation to the haplotype ATP-Binding Cassette B1 (ABCB1) which were polymorphism of C1236T, C3435T, G2677T and Glutathione S-Transferase P1 (GSTP1) A313G gene in Indonesian breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2025
2025
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Several populations in the world showed that GSTM1 gene null polymorphism and/or GSTT1 had the risk of type 2 DM (T2DM) compared with healthy control group [14], [15]. GSTT1 dan GSTM1 gene polymorphism and some diseases have been studied in Indonesia [16], [17], [18], [19], however, so far not research on T2DM. Therefore, this study was aimed to determine the role of GSTM1 and GSTT1 gene polymorphism in T2DM at Universitas Sumatera Utara Hospital, Medan, Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Several populations in the world showed that GSTM1 gene null polymorphism and/or GSTT1 had the risk of type 2 DM (T2DM) compared with healthy control group [14], [15]. GSTT1 dan GSTM1 gene polymorphism and some diseases have been studied in Indonesia [16], [17], [18], [19], however, so far not research on T2DM. Therefore, this study was aimed to determine the role of GSTM1 and GSTT1 gene polymorphism in T2DM at Universitas Sumatera Utara Hospital, Medan, Indonesia.…”
Section: Introductionmentioning
confidence: 99%